Bioaccumulation of metals in fish from hydro-accumulations on the Neretva River, Bosnia and Herzegovina used in different diets - Bobar, Denis; Huremović, Jasna; Korjenić, Enad; Selović, Alisa; Bobar, Sejit; Šehović, Elma (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
There is a growing need to assess the level of contaminants in fish as bioindicators of the health and well-being of fish and humans as its consumers. Contamination by heavy metals (Cd, Cr, Cu, Fe, Mn, Pb, Zn) was evaluated using atomic absorption spectrometer, flame and graphite furnace technique in the water samples and fish muscle tissues of Sander lucioperca, Leuciscus svallize and Tinca tinca of four hydro-accumulation lakes on the Neretva River, Bosnia and Herzegovina.Samples were collected during two seasons: autumn-winter and spring-summer (2019). It has been shown that iron (Fe) was the highest accumulating metal in fish, whilst cadmium (Cd) and lead (Pb) were the lowest. Heavy metals contents were below the maximum permissible for drinking water and for fish as prescribed by national legislation. According to correlation matrix between metals content in all fish during both fishing seasons, the highest values of the Pearson coefficient were obtained in the case of essential elements (Fe, Mn, Cu and Zn) and Fe and Mn also had a statistically significant correlation with Cd and Pb. Furthermore, potential health risk assessment exposure of the adult population in B&H revealed that none of the seven heavy metals pose risk to human health, based on the estimated daily intake via consumption of these fish species as well as target hazard quotient and hazard index values less than 1.